(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article extensively discusses the issues of improving pedagogical tolerance among master’s students using innovative technologies, new methods and techniques to improve and develop the training of pedagogical personnel in higher education institutions around the world in a competitive and rapidly developing era.